Determinants of the Women’s Labor Force Participation Rate in Indonesia - Zenia Tata Rahayu (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
Indonesia has an almost balanced population of women and men. As a developing country with a large population, it is vulnerable to problems in the large supply of labor. Women are often victims of gender inequality that restricts them from contributing to development and enjoying development. This can be seen in the participation rate of the female labor force in Indonesia which has stagnated at 50%. The purpose of this study is to analyze the factors that influence the female labor force participation rate in Indonesia in 2017-2023. The data used in this study was sourced from the Badan Pusat Statistik Indonesia. The analysis model used in this study is panel data regression with Fixed Effect Model (FEM). Based on the results of the analysis, it is known that women accessing the internet have a significant negative effect on the growth of women’s labor force participation rates, the average length of girls’ schooling and the provincial minimum wage have a significant positive effect on women’s labor force participation rates. Then foreign investment has a negative effect insignificant and domestic investment has a positive effect insignificant.